Engineering Readiness: How the TRL Figure of Merit Coordinates Technology Development. Issue 1 (2nd January 2020) - Bates, Charles Anthony; Clausen, Christian
ABSTRACT: This paper demonstrates the coordinating roles played by decision-making concepts such as Technology Readiness Level (TRL) in industrial engineering practice, where technology development is increasingly complex, involving diverse stakeholders, engineering tools and sociotechnical objects. Such distributed practices demand coordinated efforts across specialized units with diverging interests and perspectives on how development is being defined and accounted for. Nonetheless, coordinating roles of decision-making concepts in industry have largely escaped the recent attention of scholars within engineering studies and Science and Technology Studies. This paper offers an auto-ethnographic study of how the TRL figure of merit was deployed in an industrial organization. We ask how TRL is made to perform as an effective coordinating device. Following the TRL device across project meetings, we consider the three moments of a calculative device as defined by Michel Callon and Fabian Muniesa, to illuminate how TRL serves to circumscribe, configure and coordinate encounters and activity in a technology development project, as managed by the corresponding author. Contrary to linear and mechanistic understandings within management thinking, we show TRL is more than a figure of merit for measuring progress. In the hands of skilled practitioners, TRL also performs as a centralized calculating device to orchestrate distributed activities.